Evaluation of the cytotoxic effects of a new Harvard MTA compared to MTA Flow and ProRoot MTA on human gingival fibroblasts - Abdel-Rahman Youssef; Samia Elsherief (Elsevier, 2021)
Background: Biocompatibility is an essential property for any dental root repair material that may interact with the surrounding periodontal tissues. We hypothesise that the three mineral trioxide aggregate (MTA) restorative brands ProRoot MTA, MTA Flow and Harvard MTA have similar biocompatibility. To test this hypothesis, we compared the cytotoxic effects of these materials on human gingival fibroblast (GF). Methods: MTA cements were prepared, and after completion of setting, they were incubated in Dulbecco's Modified Eagle Medium for 1 day or 4 days to obtain low and high concentrations of MTA elutes respectively. The elutes of MTA supplemented with fetal bovine serum were added to GF and incubated for 3 days at 37 °C and 5% CO2. Untreated cells were used as control. The cell viability was assessed using a 3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide (MTT) assay at 24, 48 and 72 h. Results: After 24 h, the MTT assay showed that both 1- and 4-day elutes of MTA flow and Harvard MTA reduced cell viability significantly compared to control (P < 0.05). After 48 h, the 1-day elute of ProRoot MTA induced GF proliferation (P = 0.0136) while MTA flow and Harvard MTA were similar to control. After 72 h, the 1-day elute of ProRoot MTA and Harvard MTA induced GF proliferation, while the elute of MTA flow was comparable to control. The 4-day elute of Harvard MTA continued to be cytotoxic to GF after 24 h, 48 h, and 72 h incubation, while the 4-day elute of ProRoot MTA and MTA flow were similar to control. Conclusion: ProRoot MTA and MTA Flow showed comparable biocompatibility. However, the 4-day elute of Harvard MTA was cytotoxic to GF. Further studied are required to assess the cell viability after direct contact with these materials versus eluent in vitro and compare these sealers in the clinical setting.